2022
DOI: 10.17921/1415-6938.2022v26n1p32-42
|View full text |Cite
|
Sign up to set email alerts
|

Anacardiaceae na Medicina Tradicional de Comunidades Rurais do Piauí, Nordeste do Brasil

Abstract: O objetivo desta revisão bibliográfica foi levantar as espécies de Anacardiaceae utilizadas na medicina tradicional de comunidades rurais do Piauí e confrontar essas aplicações com os resultados de testes laboratoriais acerca dos efeitos biológicos de extratos desses vegetais. Para tanto, foram buscados artigos científicos nos bancos de dados: Google Scholar, Latindex, PubMed, SciELO e Science Direct. Foram incluídos nesta pesquisa os artigos publicados entre 2010 a 2019 e que revelaram os usos medicinais de p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Thus, it is one of the main therapeutic targets to prevent the entry of viruses into humans (Figure 3). Among the chemical compounds of the tested herb, agathisflavone is evidently promising for its anti-inflammatory, antibacterial, and healing properties [26]. Our study also demonstrated that agathisflavone showed potential interaction capacity with the 6VXX.…”
Section: Resultssupporting
confidence: 55%
“…Thus, it is one of the main therapeutic targets to prevent the entry of viruses into humans (Figure 3). Among the chemical compounds of the tested herb, agathisflavone is evidently promising for its anti-inflammatory, antibacterial, and healing properties [26]. Our study also demonstrated that agathisflavone showed potential interaction capacity with the 6VXX.…”
Section: Resultssupporting
confidence: 55%